Sound transmission through double cylindrical shells lined with porous material under turbulent boundary layer excitation. (24th November 2015) - Zhou, Jie; Bhaskar, Atul; Zhang, Xin
Abstract: This paper investigates sound transmission through double-walled cylindrical shell lined with poroelastic material in the core, excited by pressure fluctuations due to the exterior turbulent boundary layer (TBL). Biot׳s model is used to describe the sound wave propagating in the porous material. Three types of constructions, bonded–bonded, bonded–unbonded and unbonded–unbonded, are considered in this study. The power spectral density (PSD) of the inner shell kinetic energy is predicted for two turbulent boundary layer models, different air gap depths and three types of polyimide foams, respectively. The peaks of the inner shell kinetic energy due to shell resonance, hydrodynamic coincidence and acoustic coincidence are discussed. The results show that if the frequency band over the ring frequency is of interest, an air gap, even if very thin, should exist between the two elastic shells for better sound insulation. And if small density foam has a high flow resistance, a superior sound insulation can still be maintained.